2022
DOI: 10.3389/fonc.2022.830174
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis Combined With Experiments Predicts PUDP as a Potential Prognostic Biomarker for Hepatocellular Carcinoma Through Its Interaction With Tumor Microenvironment

Abstract: Hepatocellular carcinoma (HCC) is one of the deadliest tumors in the world and is notorious for poor prognosis. There is mounting evidence that pseudouridine performs key functions in the initiation and progression of several cancers. A previous study demonstrated that Pseudouridine 5’-phosphatase (PUDP) may be a novel prognostic biomarker in colorectal cancer. However, in the past, we have paid little attention to PUDP and we are still not clear about its function and role in cancer. In this study, a pan-canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 58 publications
(60 reference statements)
2
6
0
Order By: Relevance
“…We concluded that the TIDE composite score was not significant between the high-risk and low-risk subgroups, while MDSC, CAF expression, and risk score were significantly and positively correlated. regulatory (Treg), MDSC, and CAF (70). Next, we identified compounds that might be used to treat patients with NSCLC, and anticancer therapy with various drugs might be indicated for patients with higher risk scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We concluded that the TIDE composite score was not significant between the high-risk and low-risk subgroups, while MDSC, CAF expression, and risk score were significantly and positively correlated. regulatory (Treg), MDSC, and CAF (70). Next, we identified compounds that might be used to treat patients with NSCLC, and anticancer therapy with various drugs might be indicated for patients with higher risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that the TIDE composite score was not significant between the high-risk and low-risk subgroups, while MDSC, CAF expression, and risk score were significantly and positively correlated. Yu et al revealed a significant positive correlation between PUDP and tumor immune cell infiltration, immune cell biomarkers, and immune checkpoint expression, particularly with pro-tumor immune cells such as T cell regulatory (Treg), MDSC, and CAF ( 70 ). Next, we identified compounds that might be used to treat patients with NSCLC, and anticancer therapy with various drugs might be indicated for patients with higher risk scores.…”
Section: Discussionmentioning
confidence: 99%
“…RNA modifications play a key role in regulating cell fate, an important regulator of HCC, in tumorigenesis and disease progression (Han et al, 2018;Pea et al, 2021;Braghini et al, 2022). The m6A, m7G, m5C, m1A, m3C, and ψ RNA modifications dynamically regulate the development of HCC, providing new strategies and possibilities for selecting possible therapeutic targets and investigating precisely directed intervention strategies for future HCC therapy (Tian et al, 2019;Bolatkan et al, 2022;Liu et al, 2022;Ren et al, 2022;Tong et al, 2022;Yu et al, 2022). As the most intensively studied RNA modification, m6A, and its regulators regulate the proliferation, migration, invasion, and EMT processes of HCC cells and are promising targets for HCC therapy (Zhou et al, 2019b;Liu et al, 2020a;Wang et al, 2020b;Zhang et al, 2020c;Qu et al, 2020;Wu et al, 2020;Zhu et al, 2020;Li et al, 2021e;Wei, 2021;Gu et al, 2022;Ren et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…One study found that oxidatively modified cytoplasmic protein disulfide bond isomerase 3 (PDIA3) in HCC promoted DKC1-mediated survival of HCC and that DKC1 is a worthwhile target for HCC prediction and treatment (Ko et al, 2018). Except for DKC1, Ψ 5′phosphatase (PUDP) has been identified as a potential oncogene for HCC (Yu et al, 2022). PUDP positively correlates with tumor immune cell infiltration, and immune checkpoint expression and causes poor prognosis and a poor response to immunotherapy in HCC patients (Yu et al, 2022).…”
Section: Role Of Pseudouridine In Hepatocellular Carcinomamentioning
confidence: 99%
See 1 more Smart Citation